2020
DOI: 10.1136/tobaccocontrol-2019-055258
|View full text |Cite
|
Sign up to set email alerts
|

Price elasticity of demand for cigarettes in Bosnia and Herzegovina: microdata analysis

Abstract: BackgroundBosnia and Herzegovina (B&H) is among the top 10 countries in the world in terms of number of smokers. The cigarette prices in B&H are under a direct impact of state excise tax policy. The specific excise on cigarettes was introduced in B&H in 2009. Since then it has been increasing every year thus being the main driver of cigarette prices growth.MethodsIn this paper we estimate price elasticity of demand for cigarettes following Deaton demand model and apply it on microdata obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…During that period some major changes in tobacco taxation policy had happened that led to singificant increase in cigarette prices (Aljinović Barać et al, 2018). Nevertheless, the obtained result falls within the range of unconditional cigarette price elasticities for comparable studies using Deaton's methodology (from −0.5 for Vietnam (Eozenou & Fishburn, 2009) to −1.4 for Bosnia and Herzegovina (Gligorić et al, 2020). The symmetry-unrestricted estimates provide similar results.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…During that period some major changes in tobacco taxation policy had happened that led to singificant increase in cigarette prices (Aljinović Barać et al, 2018). Nevertheless, the obtained result falls within the range of unconditional cigarette price elasticities for comparable studies using Deaton's methodology (from −0.5 for Vietnam (Eozenou & Fishburn, 2009) to −1.4 for Bosnia and Herzegovina (Gligorić et al, 2020). The symmetry-unrestricted estimates provide similar results.…”
Section: Resultssupporting
confidence: 79%
“…To the best of authors' knowledge, there are only several studies using Deaton's methodology to estimate the price elasticities of cigarettes and tobacco. Price elasticity estimates from these studies vary considerably, and the most range from -0.2 to -1.4 (Chavez, 2016;Chelwa & Walbeek, 2019;Chen & Xing, 2011;Eozenou & Fishburn, 2009;Gligorić et al, 2020;John, 2005John, , 2008Mugosa et al, 2020;Salti et al, 2015;Vladisavljevic et al, 2020). However, it should be noted that some of these studies considered all households in the budget share regression, some considered only households with positive purchases, and some were not explicit about this matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for continuing to smoke in different situations is that smokers can change their brand to pay less but still receive their needed nicotine to suppress withdrawal symptoms and provide positive effects such as increased energy and attention. Indeed, the availability of affordable substitute products is a reason for the high price elasticity of demand for cigarettes [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…5 6 Previous research that was based on the data from Household Budget Survey (HBS) and conducted in B&H in 2011 and 2015, and the Deaton demand model, 7 showed that if cigarette prices in B&H increased by 10%, the demand for cigarettes would decrease by 13.66%. 8 Since the main driver of the increase in cigarette prices in B&H over the last decade has been the increase in excise taxes, the high response rate of cigarette demand to price increase indicates that increase in excise taxes is an effective tobacco control policy. However, defining the most appropriate tobacco tax and other polices requires an analysis of the effects of this policy on the smoking prevalence, smoking consumption of different socioeconomic groups, as well as on public revenue.…”
Section: Introductionmentioning
confidence: 99%